MEASURES TO SUPPORT THE FRUIT AND VEGETABLE SECTOR BY THE STATE (American Journal of Interdisciplinary Research and Development, 2024)
In the article, the cluster method of production in agriculture has been established, the size of the agricultural areas divided into clusters by crop types is 67% in cotton and textile, 8% in animal husbandry, and 7.5% in fruit and vegetable growing. it is analyzed that serious attention should be paid to the organization of interest.